CUMULATING PROCESSES AT THE CRUST-MANTLE TRANSITION ZONE INFERRED FROM PERMIAN MAFIC-ULTRAMAFIC XENOLITHS (PUY BEAUNIT, FRANCE) - Berger Ju.; Féménias O.; Coussaert N.; Mercier J.C.; Demaiffe D. (My University, 2007)
Ultramafic and mafic xenoliths of magmatic origin, sampled in the Beaunit vent (northern French Massif Central), derive from the Permian (257 Ma) Beaunit layered complex (BLC) that was emplaced at the crust-mantle transition zone (~1 GPa). These plutonic xenoliths are linked to a single fractional crystallisation process in four steps: peridotitic cumulates; websteritic cumulates; Al-rich mafic cumulates (plagioclase, pyroxenes, garnet, amphibole and spinel) and finally low-Al mafic cumulates. This sequence of cumulates can be related to the compositional evolution of hydrous Mg basaltic magma that evolved to high-Al basalt and finally to andesitic basalt. Sr and Nd isotopic compositions confirm the co-genetic character of the various magmatic xenoliths and argue for an enriched upper mantle source comparable to present mantle wedges above subduction zones. LILE, LREE and Pb enrichment are a common feature of all xenoliths and argue for an enriched sub-alkaline transitional parental magma. The existence of a Permian magma chamber at 30 km depth suggests that the low-velocity zone observed locally beneath the Moho probably does not represent an anomalous mantle but rather a sequence of mafic/ultramafic cumulates with densities close to those of mantle rocks.
Keywords: XENOLITHS; ULTRAMAFIC-MAFIC; SUB-ALKALINE CUMULATE; FRACTIONAL CRYSTALLISATION; CRUST-MANTLE TRANSITION; Permian; Paleozoic::Permian; Палеозой::Пермская